Effect of different mulchings in Prunus persicae var. Opodepe. - FLORES, P. (Universidad Nacional del Litoral, 2019)
The objective was to determine the effect of mulchings on the growth of peach var. Opodepe in the south of Santa Fe. The variables evaluated were soil water content, pH, electrical conductivity (EC) and crop growth. The soil water content reached the highest values in organic mulching, there being no significant differences with respect to inorganic. The registered pH values wasn’t compromise the development of the peaches. EC increased in inorganic mulching, but with non-limiting values for crop development. The growth variables showed the best results in inorganic mulching. This management ensures an efficient establishment of the crop because it allows an excellent control of weeds without resorting to chemical or mechanical control, while is recommended to use organic mulching only when the fruit tree is established. rs considered. So it is possible to conclude that TCQ inclusion in the conditions and dose used did not report any benefit in the parameters evaluated).